Pioneering Inclusive Schools: The Role of School Principals in Realizing Freedom of Learning - Yusup, Muhammad; Ansori, Kholid; Nasution, Fitri; Nur'aini, Nur'aini; Maula, Linziatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research aims to analyze the role of madrasa heads in realizing independent learning in inclusive schools in madrasah. This study uses a case study-type qualitative research approach. Data collection techniques are carried out through interviews, observation and documentation. Data analysis is carried out circularly, from data reduction to data presentation and conclusion. The main findings of this research include changes in teaching and learning methods that are more inclusive, the use of digital resources to expand access to education, and the development of collaborative learning that supports learner-centred learning. The results of this research show that madrasah that adopt digital information technology can increase the accessibility of Islamic education for various levels of society by providing technological infrastructure, increasing human resource capacity, implementing digital learning and continuous evaluation. This research provides implications regarding the importance of inclusive approaches and digital information technology in realizing the